Enhancing the mechanical, wear behaviour of copper matrix composite with 2V-Gr as reinforcement. (July 2021) - Jabinth, J; Selvakumar, N
In the present study, copper along with secondary hybrid reinforcements like Vanadium (V) and Graphene-L (Gr-L) with various proportions like pure Cu, Cu-2V, Cu-2V-0.5Gr, Cu-2V-1Gr, Cu-2V-1.5Gr are added to evaluate the behaviour of Copper Matrix Composite. The evenly dispersion of heterogeneous Copper Matrix Composite is achieved by the economical stir casting process. The heterogeneous mixture with metallic materials is a promising strategy to improve the properties of CMC. The prepared specimen is subjected to various testing processes to test the properties like Tensile strength, hardness, Yield strength, Impact strength and wear behaviours. The grain formation of hybrid CMC is also studied using an optical microscope to see the relationship between strength and grain size. The characterization of hybrid CMC is done by X-ray diffraction, Fourier Transform Infrared Spectroscopy and Energy Dispersive X-ray Spectroscopy. Fractography is also done to investigate the debonding mechanism of heterogeneous composites. The wear behavior of the hybrid composite is examined by Pin-on-disc tribometer. The results obtained, shows that, there is a reduction in grain size with the increase in addition of vanadium and graphene-L. The decrease in grain size has directly contributed to the improvement of mechanical properties of CMC. There is also an enhancement in wear behavior such as improvement in co-efficient of friction and wear resistance with increase in hybrid composition. This paves a new strategy and acts as a reliable reinforcement to improve the behaviour of copper based metal matrix composites.